Validation, Diagnostic, and Monitoring Roles of Multiomic Studies in Putative Immunotoxiepigenetic Models of Immune-Mediated Inflammatory Diseases - Michael T. Okafor (International Journal of Medicine and Health Development)
Immune-mediated inflammatory diseases (IMIDs) are mediated by immune dysfunction. Putative models of T-cell-mediated immune dysfunction in IMIDs exist and are yet to be validated by multiomics studies. Prompt diagnosis and monitoring are crucial for IMID management. The aim of this review was to discuss the putative T-cell dysfunction model of IMIDs and the role of multiomics studies for validation of the disease models as well as its diagnostic and monitoring potential in IMIDs. Online searches on databases such as Google Scholar, PubMed, Biomed Central, and SciELO were carried out. An attempt was made to review articles with keywords such as genomics, proteomics, transcriptomics, metabolomics, T cell immunopathogenesis/dysfunction, immune dysfunction, and IMIDs. The putative T-cell dysfunction model of IMIDs and its validation with multiomics studies were discussed. The diagnostic and monitoring roles of multiomic studies for management of IMIDs were also discussed. The review concluded that multiomic studies have validating potential for the putative T-cell dysfunction model of IMIDs as well as diagnostic and monitoring roles in IMIDs.